PREVALENSI DIABETES MELLITUS TIPE 2 PADA ANAK DAN REMAJA (STUDI LITERATUR) - Gangga Mahatma; Wisda Widiastuti; Riki Nova; Anita Darmayanti; Abdullah, Dessy (Yayasan Nusantara Hasana Berdikari, 2024)
Type 2 Diabetes Mellitus is a long-term medical illness marked by high blood sugar levels caused by the body's ineffective use of insulin. The increasing frequency of this problem in not just adults but also in children and adolescents is causing alarm. An overview of Type 2 Diabetes Mellitus detection, diagnosis, treatment, and risk factors is intended to be provided by this review of the literature. The review's research sources come from a number of respected scientific periodicals.The information included in this literature review comes from a variety of scientific papers that have been published in the recent five to ten years in both domestic and foreign journals. Using the following keywords, a comprehensive search of several databases, including PubMed, the Cochrane Library, and Google Scholar, produced these articles: